Study on the Effect of Diamond Grain Size on Wear of Polycrystalline Diamond Compact Cutter - Abdul-Rani, A.M. (Institute of Physics Publishing, 2018)
Drilling operation is one of the most crucial step in oil and gas industry as it proves the availability of oil and gas under the ground. Polycrystalline Diamond Compact (PDC) bit is a type of bit which is gaining popularity due to its high Rate of Penetration (ROP). However, PDC bit can easily wear off especially when drilling hard rock. The purpose of this study is to identify the relationship between the grain sizes of the diamond and wear rate of the PDC cutter using simulation-based study with FEA software (ABAQUS). The wear rates of a PDC cutter with a different diamond grain sizes were calculated from simulated cuttings of cutters against granite. The result of this study shows that the smaller the diamond grain size, the higher the wear resistivity of PDC cutter. Â© Published under licence by IOP Publishing Ltd.